Risk of Male Infertility Due to Testosterone Replacement Therapy for Late-Onset Hypogonadism (LOH) - Sukegawa, Gen (Hinyokika kiyo. Acta urologica Japonica, 2020)
Testosterone replacement therapy is widely used for the treatment of late-onset hypogonadism (LOH). However, because exogenous testosterone can suppress the hypothalamic-pituitary-gonadal axis through negative feedback, testosterone replacement therapy may lead to secondary spermatogenic failure and subsequent infertility. We report our experience with male infertility in patients who had received testosterone for LOH. Six of the 4,375 patients who visited our clinic for infertility evaluation had received testosterone replacement therapy for LOH. In these patients, testosterone was administered for 3 to 12 months. In 5 of these 6 patients, blood levels of gonadotropins were markedly suppressed, suggesting hypogonadotropic hypogonadism. In the remaining 1 patient, blood luteinizing hormone and follicle stimulating hormone levels were within the standard reference ranges, but the testosterone level was elevated. Semen findings in these patients ranged from azoospermia to severe oligospermia. Testosterone administration was immediately stopped in all patients. Of the 3 patients who needed prompt recovery of spermatogenesis, 2 received human chorionic gonadotropin (hCG) injection and 1 received clomiphene orally. Semen findings were significantly improved in all patients, except one who was treated with hCG for only one month. Although recovery of spermatogenesis is generally favorable after cessation of testosterone replacement therapy, the recovery period is highly variable among patients. Clinicians treating LOH must recognize that testosterone administration is contraindicated in men who desire to maintain future fertility. LOH patients who wish to preserve fertility should be considered for treatment with clomiphene or hCG